Tourism, the SDGs and partnerships. Issue 10 (9th August 2022) - Scheyvens, Regina; Cheer, Joseph M.
Abstract: In 2019, Massey University in New Zealand hosted the world's first research conference on tourism and the Sustainable Developments Goal (SDGs). The aims of this conference were to bring together a wide range of stakeholders to discuss (i) challenges to tourism contributing to the SDGs, and (ii) ways in which tourism can deliver on its potential to be more inclusive, equitable and sustainable. The need for diverse actors to work in partnership to achieve the SDGs emerged as a key theme. This special issue presents several of the papers from that conference, as well as contributions from a broader range of scholars. As is evident in this collection, partnerships in tourism tend to be complex, multi-faceted, subject to multiple legal frameworks and governance arrangements, and are often cross-sectoral, transnational and cross-border. While these overlapping factors can make it challenging for tourism actors to develop effective partnerships to deliver on the SDGs, the articles herein suggest there is considerable promise where stakeholders have shared values and commitments. Tourism scholars need to reflect more on possibilities for constructive partnerships because, as the pandemic milieu has demonstrated, partnerships spanning governments, industries and communities are a fundamental requirement to producing more sustainable tourism futures.